[Kinetics and mechanisms of hypochlorite oxidation of α-amino acids at the time of water disinfection] - Alouini, Z; Seux, René (Water Research, 1987)
International audience In the field of water treatment, one increased concern over the quality of the environment requires an understanding of the fate of compounds generated by the addition of chemicals. One area of considerable interest is the stability of chlorine compounds produced when chlorine is added to natural water or swimming pool water. It is desirable to be able to predict the lifetimes of these harmful compounds under various conditions. In this study we examine for a range of hypochlorite α-amino acid ratios and pH, the kinetics and mechanism of the decomposition of α(N-chloro) and α(N,N-dichloro) amino acid, one of the products of chlorination.The interaction of chlorine with amino acids has been studied by several investigators Langheld (1909) was the first who discussed the decomposition of the α(N-chloro) amino acids. He noted that hypochlorous acid salts react with α-amino acids in the same manner as they do with amines to form monochlorinated or dichlorinated derivatives. Then, the decomposition of chloro-amino acids leads to the corresponding aldehydes or ketones, ammonia, carbonic acid, and sodium chloride. As an intermediate step Langheld assumed an imine formation.Wright (1936) and Pereira et al. (1973) have investigated the decomposition products of α(N,N-dichloro) amino acids. Their results indicate rapid formation of carbon dioxide, chloride ion, and the corresponding nitrile.Recently, many authors have investigated the rates of α(N-chloro) amino acids decomposition and the stability of its products (William and Wendy, 1979; Yoshiro et al., 1980; Le Cloirec-Renaud, 1984). However, they have neither differentiated between the decomposition of α(N-chloro) amino acid and α(N,N-dichloro) amino acid, nor have they demonstrated the combined effect of pH and molar ratio of hypochlorite and α-amino acid.In this study the hypochlorite oxidation of simple α-amino acids in aqueous solution has been investigated in the dark. The concentration of α(N-chloro) amino acid and α(N,N-dichloro) amino ...